2004
DOI: 10.1038/sj.ejhg.5201242
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic structure of the human nebulin gene and identification of alternatively spliced transcripts

Abstract: The giant nebulin protein is a fundamental structural component of the thin filaments of the striated muscle sarcomere. Nebulin binds to actin and the size of nebulin correlates with actin filament length, suggesting that nebulin may determine the length of the thin filaments during myofibrillogenesis. We have previously described the genomic organization of the 3 0 end of the nebulin gene (NEB), and identified 18 different NEB mutations in patients with autosomal recessive nemaline myopathy. Here we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 24 publications
6
134
0
Order By: Relevance
“…The heterozygous NEB mutation c.24372_24375dup (p.Val8126fs) in exon 172 is predicted to result in a frame shift and a premature stop codon. Donner et al 17 demonstrated that there are four regions of the Nebulin gene which exhibit alternative splicing. Exon 172 is located in the furthest distal of these, exons 166-177, which exhibits an extremely high degree of isoform variability in some tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterozygous NEB mutation c.24372_24375dup (p.Val8126fs) in exon 172 is predicted to result in a frame shift and a premature stop codon. Donner et al 17 demonstrated that there are four regions of the Nebulin gene which exhibit alternative splicing. Exon 172 is located in the furthest distal of these, exons 166-177, which exhibits an extremely high degree of isoform variability in some tissues.…”
Section: Discussionmentioning
confidence: 99%
“…NEB encodes nebulin, a protein of B800 KDa. 1,2 Although the precise function of nebulin is not fully understood, observations in gene knock-out animals suggest that it has a role in the regulation of thin filament length and muscle contraction. 3 Typical NEB-related NM is of infantile-onset and static or only slowly progressive, affecting the axial, facial, bulbar and proximal limb muscles.…”
Section: Introductionmentioning
confidence: 99%
“…We are still confident that most are coding exons, since a region composed of 11 of these exons was identified by Donner et al in a minor splice form. 13 …”
Section: Domains and Exons In Nebulin Genesmentioning
confidence: 99%
“…Donner et al suggested that this LINE-2 could be responsible for the duplication event. 13 It should be noted that the duplicated region is not part of a major splice form and that it has only been seen in fetal transcripts. 13 Thus, the functional implications of this duplication are unclear.…”
Section: The Nebulin Gene In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation